Estado, recursos naturales y política ambiental: notas para el caso peruano - Lanegra, Iván (2013)
This article is divided into three main sections that seek to provide a panoramic look at the relationship between the presence of important natural  resources in the country and  how this influences the state, particularly in the development of environmental policies. In that sense, in the first part, we made a theoretical introduction to the  relationship between natural resource abundance  and  state building,  with a brief mention of the  ‘natural resource curse’. Following is a particular case of Peru and the particularities of the  exploitation of their natural resources. Then we go on to explain how, through various factors,  including social conflicts, have created conditions for institutional innovation in environmental matter